Comparison of WC and SiO 2 mill additives for abrasion resistance sodium borosilicate glass-ceramics coating - Yilmaz, Yasin Bozkurt; Karaahmet, Oguz; Cicek, Bugra (KOREAN ASSOC CRYSTAL GROWTH, INC, 2024)
Vitreous enamel (glass-ceramic) coatings are used to improve surface properties of metals due to their chemical and high temperature resistance. With the widespread use of enamelled products, it is necessary to develop enamels with high abrasion resistance, which protects their performance in abrasive environment such as scratches and friction damage. In this study, tungsten carbide (WC) and quartz (SiO 2 ) were added as mill additives into the enamel composition in proportions ranging from 0 wt.% to 8 wt.%. An XRD analysis was performed to examine the effects of additives on crystal phases. Depending on the additive type, SiO 2 , CaWO 4 and WC phases were observed. The batches were applied on cast iron. The abrasion resistance of the enamelled cast iron surfaces were investigated by PEI test (ISO 10545-7). An SEM-EDS analysis were carried out to investigate the fracture mechanism and the effects of addition on the microstructure. The analyses reveal that surface morphology and abrasion resistance of the enamel coatings change depending on the mill additive rate. With 8 wt.% WC and 8 wt.% SiO 2 addition, the abrasion resistance was improved by 51.80% compared to the standard sample.
Keywords: Enamel; Glass ceramics; Abrasion resistance; Additive; Surface properties; Materials Science